A vacationer-driven approach to understand destination image: A Leximancer study. (April 2015) - Tkaczynski, Aaron; Rundle-Thiele, Sharyn R; Cretchley, Julia
Destination image studies have largely centred upon conceptualizing destination image through a variety of methods that are predominantly researcher driven. Whilst this has furthered our understanding of how vacationers perceive a destination(s) on key reference criteria, the researcher-driven process may artificially increase the salience of some attributes. The purpose of this study was to showcase how a vacationer-driven approach employing Leximancer may be used to understand destination image by enabling vacationers to drive the attributes and sentiments of importance. Based on a sample of 517 vacationers to the Fraser Coast, respondents were able to identify nine themes. Theoretical, methodological and practical implications are presented and recommendations and future research opportunities are outlined.